Prevalence and Incidence of Latent Tuberculosis Infection in Georgian Healthcare Workers - A. Whitaker, Jennifer (Public Library of Science, 2013)
BACKGROUND: Tuberculosis is a major occupational hazard in low and middle-income countries. Limited data exist on serial testing of healthcare workers (HCWs) with interferon-γ release assays (IGRAs) for latent tuberculosis infection (LTBI), especially in low and middle-income countries. We sought to evaluate the rates of and risk factors for LTBI prevalence and LTBI test conversion among HCWs using the tuberculin skin test (TST) and QuantiFERON-TB Gold In-tube assay (QFT-GIT). METHODS: A prospective longitudinal study was conducted among HCWs in the country of Georgia. Subjects completed a questionnaire, and TST and QFT-GIT tests were performed. LTBI testing was repeated 6-26 months after baseline testing. RESULTS: Among 319 HCWs enrolled, 89% reported prior BCG vaccination, and 60% worked in TB healthcare facilities (HCFs). HCWs from TB HCFs had higher prevalence of positive QFT-GIT and TST than those from non-TB HCFs: 107/194 (55%) vs. 30/125 (31%) QFT-GIT positive (p<0.0001) and 128/189 (69%) vs. 64/119 (54%) TST positive (p = 0.01). There was fair agreement between TST and QFT-GIT (kappa = 0.42, 95% CI 0.31–0.52). In multivariate analysis, frequent contact with TB patients was associated with increased risk of positive QFT-GIT (aOR 3.04, 95% CI 1.79–5.14) but not positive TST. Increasing age was associated with increased risk of positive QFT-GIT (aOR 1.05, 95% CI 1.01–1.09) and TST (aOR 1.05, 95% CI 1.01–1.10). High rates of HCW conversion were seen: the QFT-GIT conversion rate was 22.8/100 person-years, and TST conversion rate was 17.1/100 person-years. In multivariate analysis, female HCWs had decreased risk of TST conversion (aOR 0.05, 95% CI 0.01–0.43), and older HCWs had increased risk of QFT-GIT conversion (aOR 1.07 per year, 95% CI 1.01–1.13). CONCLUSION: LTBI prevalence and LTBI test conversion rates were high among Georgian HCWs, especially among those working at TB HCFs. These data highlight the need for increased implementation of TB infection control measures.